Crosstalk between cytokinin and ethylene signaling pathways regulates leaf abscission in cotton in response to chemical defoliants. (4th February 2019) - Xu, Jiao; Chen, Lin; Sun, Heng; Wusiman, Nusireti; Sun, Weinan; Li, Baoqi; Gao, Yu; Kong, Jie; Zhang, Dawei; Zhang, Xianlong; Xu, Haijiang; Yang, Xiyan
Abstract : Enhanced cytokinin signaling results in delayed defoliation and a reduced response to ethylene in cotton treated with thidiazuron and ethephon, with crosstalk between cytokinin and ethylene signaling playing an important regulatory role. Abstract: Abscission is a process that allows plants to shed tissues or organs via cell separation, and occurs throughout the life cycle. Removal of leaves through the use of chemical defoliants is very important for mechanical harvesting of cotton ( Gossypium hirsutum ). However, our knowledge of the molecular mechanisms of the defoliation response involved is limited. In this study, RNA-seq was conducted in order to profile the differentially expressed genes (DEGs) between cultivars X50 (sensitive to chemical defoliants) and X33 (relatively insensitive) at different time points after treatment with thidiazuron and ethephon (TE). A total of 2434 DEGs were identified between the two cultivars across the different time-points. Functional categories according to GO and KEGG analyses revealed that plant hormone signal transduction and zeatin biosynthesis were involved in the response to TE. Cytokinin oxidase/dehydrogenase (CKX) genes and ethylene-related genes were up-regulated following TE treatment, and were associated with increased level of ethylene, especially in cultivar X50. Down-regulation of GhCKX3 resulted in delayed defoliation and a reduced ethylene response. The results show that crosstalk between cytokinin and ethylene regulates cotton defoliation, and provide new insights into the molecular mechanisms underlying the mode of action of defoliants in cotton.